On the thermal ecology of two coexisting lizard species (Reptilia, Lacertidae) in a hot and dry area of Bulgaria - Emiliya Vacheva; Nikola Stanchev; Georgi Krastev; Angel Dyugmedzhiev; Borislav Naumov (Herpetozoa)
Thermal ecology plays a key role in shaping the behavior and distribution of reptiles, particularly under climate stress. Understanding how sympatric lizard species manage their thermal preferences is essential for predicting their responses to changing climate. We studied thermo-ecological parameters in two lizard species, Lacerta viridis and L. trilineata that occur under syntopy in SW Bulgaria. We recorded in situ body, air and substrate temperatures, humidity and UV radiation for 190 individuals. Both species maintained body temperatures higher than air and substrate temperature. Comparison of the two species showed statistically significant differences between them in terms of body and substrate temperature, with a trend towards higher values in L. viridis. For L. trilineata, statistically significant differences were found only between immatures and females in terms of substrate temperature (higher values in females). For L. viridis, there were significant differences between immatures and males in each of the temperature parameters (with a trend for higher values in males) as well as between immatures and females in air temperature (higher values in females). No significant differences were found in humidity or UV exposure among groups. Our findings reveal species- and sex-specific thermal strategies in two co-existing lacertids, likely reflecting different ecological or physiological demands. The results provide valuable baseline data for predicting species responses to increasing temperatures in hot and dry habitats.